Human-Elf Marriage as Formula in Popular Fantasy - Mahardhika Kusumo Simbolon (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2023)
Understanding how stories of human-elf marriages are portrayed is very crucial because such stories can influence the public’s opinion regarding people who claim to have such relationships. Therefore, a study on human-elf marriage as a formula in popular fantasy contributes to a better understanding of the function and role of popular fantasy in society. Using Cawelti’s theory of formula (Cawelti, 1977) as starting point, this study tries to see how human-elf marriage as a formula may be portrayed differently in English fantasy works and popular Javanese stories. Several English fantasy works are presented as data for this study, along with Javanese stories collected from social media, television, and the box office that have strong influences from urban legends. Stories from the Arabian peninsula are also considered for their strong affinity to the predominantly Islamic society of Java. Miles & Huberman (1992) qualitative methods are applied interactively and continuously to optimize the data collection and analysis. The analysis shows that the portrayal of marriages between humans and Other beings, such as elves, fairies, or jinns, hugely depends on the manner of the depiction of Other beings involved. The elves of Tolkien are strongly associated with the heavenly light that humans long for, while the jinns in the Islamic and Javanese traditions are generally considered bearers of turmoil in human society. Consequently, the human-elf marriages of Tolkien are celebrated. All kinds of contact between humans and the jinns, however, fairy-like they may be, are avoided and even condemned in Javanese stories. This conclusion confirms that the formula in popular fantasy serves as both an endorsement or a condemnation of certain notions a particular society upholds.